142k views
3 votes
What are the solutions to this quadratic equation? x^2+6x-5=0

User Sharyn
by
5.2k points

1 Answer

2 votes

Answer:


x = -3+√(14) \\x=-3-√(14)

Explanation:

x + 6x - 5 = 0

Since you can't factor the equation, use the quadratic formula.

Your equation is already in the form of ax + bx + c.


x=\frac{-b\frac{+}{} \sqrt{b^(2) -4ac} }{2a}

Based on your equation a = 1 b = 6 c = -5. Plug in the numbers and solve for x.


x = \frac{-6\frac{+}{} \sqrt{6^(2) -4(1)(-5)} }{2(1)} \\x = \frac{-6\frac{+}{} √(36+20 ) }{2} \\x=\frac{-6\frac{+}{}√(56) }{2} \\x=\frac{-6\frac{+}{}2√(14) }{2} \\\\x = -3+√(14) \\x=-3-√(14)

User Trh
by
4.7k points